International Migration and Turnout Bias - Wigginton, Michael J.; Stockemer, Daniel; van Schouwen, Jasmine (Université d'Ottawa | University of Ottawa, 2019)
Focusing on two commonly used indicators of turnout, VAP turnout (the number of votes cast as a percentage of the population of voting age) and RV turnout (votes cast as a percentage of the number of registered voters), this article discusses possible biases induced by migration flows. Using a global dataset on elections in over 100 democracies between 1990 and 2012, we test the potential bias induced by the percentage of resident non-citizens and nationals living abroad on VAP and RV turnout, respectively. Through time series cross sectional analysis, we find that the number of resident non-citizens does negatively bias VAP turnout, to the extent that a country with 10 percent non-citizen residents would have turnout underreported by nearly 4 percentage points. In contrast, we find that the number of nationals living abroad does not induce a turnout bias.
Keywords: VAP turnout; RV turnout; measurement; bias; immigration; migration